Prevalence and factors associated with metabolic syndrome in 6-10-year-old children - Alynne Christian Ribeiro Andaki; Edmar Lacerda Mendes; Ciro Jose Brito; Paulo Roberto dos Santos Amorim; Rachel Wood; Adelson Luiz Araújo Tinoco (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: to identify the prevalence of metabolic syndrome (MetS) and associated risk factors in children. Methods: a total of 1,480 Brazilian children aged 6-10 years old (52.2% girls) participated in this population-based, epidemiological cross-sectional study. The inclusion criteria were children born between the years 2001 and 2006, of both sexes, who did not use remedy, were not on a calorie restriction diet, and who respected the 12-hour fast for blood collection. Anthropometric measurements, blood pressure, blood collection, and completion of the Previous Day Food Questionnaire and interview using a Physical Activity List were held at school. Parents were asked to complete a questionnaire on socioeconomic status and lifestyle habits of their child. Chi-square test compared proportions and factors associated with MetS were identified using Poisson Regression. Results: Girls had significantly higher MetS prevalence compared with boys (12.6% vs. 8.5%, p=0.046). After multivariable analysis, body fat percentage (p=0.001), fat mass (p<0.001), lean body mass (p< 0.001) and sedentary behavior (p= 0.050) were positively associated with MetS. Conclusions: Modifiable factors such as body fat percentage, fat mass, lean body mass and sedentary behavior were associated with MetS in children. Thus, interventions targeted for weight management, and adopting healthy habits such as reducing time in front of TV/computer/video game need to be part of the lifestyle of children.